POTENSI LAHAN UNTUK BUDIDAYA PISANG DI KECAMATAN JENAWI KARANGANYAR - Mujiyo, Mujiyo; Widijanto, Hery; Herawati, Aktavia; Rochman, Fatchur; Rafirman, Rizkisadi (Universitas Sebelas Maret, 2017)
Banana (Musa spp.) is a tropical fruit that is widely grown in Indonesia as it beneficially increases the farmers’ welfare. However, the wider scale of suitable land still needs to be developed. This study aims to know the distribution of suitable locations for banana cultivation in Jenawi based on the climate conditions. The research was done by making soil map unit, characterizing land’s climate, matching climate conditions with plant growth requirements, and then mapping the suitable location for banana cultivation. The results showed that the agriculture’s climate suitability in Jenawi is classified into two areas: (1) middle - upper/eastern area (not suitable for banana cultivation as it is located in the high area of 2,056 masl with the low temperature 13.8°C and the high rainfall 3,750 mm/year); (2) middle - lower/west area (suitable for banana cultivation as it is located in the lower area of 610 masl with the higher temperature 22.6 °C and lower rainfall 3,333 mm/year. So that the banana plants are potentially developed in the middle - lower/west area of Jenawi i.e. in the Village of Trengguli, Sidomukti, Balong, Lempong, Menjing and Seloromo. The determination of the land suitability class in detail and in terms of the characteristics and quality of the soil can be more focused on the area which suitable climate conditions in order to obtain the land suitability class, limiting factors and improvement efforts.